Social Commerce: The Impact of Satisfaction on Purchase Intention in Local Business - Zoe M. MATOS; Triana A. POSTIGO; Martin A. MAURICIO (Communications of International Proceedings, 2022)
The theoretical understanding of social commerce and the factors that influence it have received attention in recent years, due to the new way of acquiring different products through social networks. This study aims to investigate the relationship between information quality, service quality and social support with customer satisfaction, and how it influences purchase intention within social commerce. For the research, 306 people were surveyed, using a non-probabilistic sampling. The sample is made up of men and women who made purchases through social networks to businesses in the last 3 months. A PLS-SEM structural model was used to examine the relationship between the constructs. The results showed that both the quality of information and the quality of service and social support have a positive impact on satisfaction, influencing purchase intention.
Keywords: Social Commerce; satisfaction; purchase intention; information quality; service quality and social support.